2017
DOI: 10.1007/s12306-017-0528-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Medicaid payer status on patient outcomes following repair of massive rotator cuff tears

Abstract: Medicaid coverage will expand to millions of uninsured Americans under current healthcare reform. Medicaid patients with massive RCT appear to significantly improve with surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…When looking at other types of orthopedic procedures, similar results have been demonstrated in patients with rotator cuff pathology. Sabesan et al 22 found opposite results in patients with massive rotator cuff tear, whereby patients with Medicaid and Medicare had equivalent improvements in postoperative outcome measure when compared with those with private insurance. Although, they did observe less follow-up rates among patients with Medicaid insurance.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at other types of orthopedic procedures, similar results have been demonstrated in patients with rotator cuff pathology. Sabesan et al 22 found opposite results in patients with massive rotator cuff tear, whereby patients with Medicaid and Medicare had equivalent improvements in postoperative outcome measure when compared with those with private insurance. Although, they did observe less follow-up rates among patients with Medicaid insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Further, worse postoperative outcomes associated with low SES persist in orthopedic surgeries, such as total joint arthroplasties 13,59 and spine surgery 31,35 . Several studies observe similar trends in care for rotator cuff tear 8,12,24,30,39,44,48 .…”
mentioning
confidence: 83%
“…Sabesan, et al 48 , finds that functional outcomes are worse for low SES patients, however Jain, et al 24 , does not find significant disparity when highest education level is used as the measure. This variance highlights the reality that healthcare disparity is a complex problem, not easily explained by small-scale studies.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…5-9 Studies in multiple surgical fields have shown insurance status can be a predictor of poor outcomes following surgery, as patients with government-sponsored insurance experience more complications and increased mortality following surgery. 10-16 Additionally, lower SES has been linked to higher levels of patient-reported pain. 6-9 As Medicaid is primarily utilized by lower SES patients, these studies lend support to the anecdotal finding that Medicaid patients experience more preoperative pain and less pain relief following surgery than those with private insurance.…”
Section: Introductionmentioning
confidence: 99%